Vitamin D and hypertension - Pawlicka, Marta; Fałkowska, Urszula; Bałabuszek, Kamil; Radzka, Agnieszka; Mroczek, Anna; Bednarski, Jerzy (Journal of Education, Health and Sport, 2018)
Introduction: Current epidemiological studies indicate, that insufficiency of vitamin D affects 50% of the population worldwide. 1α,25(OH)2D – active form of vitamin D affects tissues and organs through vitamin D receptor (VDR). Attention to the role of vitamin D deficiency in hypertension development has been continuously increased during recent decades. The aim of the study: The purpose of this narrative systemic review was to analyse and summarize available data on role of vitamin D deficiency in hypertension development.Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar database was carried out using the following keywords: hypertension, calcitriol, vitamin D, 25-hydroxyvitamin D. Description of the state of knowledge: Vitamin D influence blood pressure level through renin-angiotensin-aldosterone system (RAAS) and parathormon regulation. Studies conducted on animal model could explain possible mechanism of vitamin D influence on blood pressure control. However, clinical trial results are equivocal due to differences in sample size, heterogeneity of patient baseline characteristics, different vitamin D doses and study duration.Summary: Further research is needed to confirm the role of vitamin D in hypertension development.